How Adults With Serious Mental Illness Learn and Use Wellness Recovery Action Plan's Recovery Framework. (March 2021) - Petros, Ryan; Solomon, Phyllis
This study was conducted to investigate how adults with serious mental illness learn and utilize an illness self-management framework for pursuing recovery through a program called Wellness Recovery Action Plan (WRAP). The researchers employed an interpretive descriptive methodology with thematic analysis. Data were collected from three focus groups ( n = 26) and in-depth interviews with follow-up member checks with 10 participants ( n = 20 interviews). Findings aligned with main constructs of self-determination theory (SDT) to explain how an autonomy-supportive environment created opportunities for participants to build competency, implementing personalized recovery strategies that are socially endorsed by peers, resulting in internalized motivation for continued application of WRAP's framework. SDT appears to explain mechanisms of change for WRAP. Recommendations for mental health organizations include broadly ensuring autonomy-supportive environments and services that maximize opportunities to build competence in recovery strategies in collaboration with peers. Future research may utilize SDT as the theoretical basis for investigating self-management programs.